ANALYSIS OF EFFECTIVENESS, EFFICIENCY AND CONTRIBUTION TO INCREASE TAX REVENUE IN THE ORIGINAL REGIONAL (A case study in KPPD of Yogyakarta) - Safitri, Dian; Legowo.,M.Si.,Akt, Drs. H.Herman (Accounting, 2009)
A very large dependence of the local to central government lead to creativity in managing economic resources can not develop optimally. High dependence on revenue from the center on one side and the low role of Regional Income on the other hand a consequence of the low capacity of the region income to finance local expenditures. Conditions such as these, of course, complicate the regional government to implement in practice. Based on the analysis and discussion of the research is concluded, the level of effectiveness of local tax collection by the city of Yogyakarta KPPD highly variable and ranges. Regarding the level of analysis that compares the cost efficiency of tax collection area to the realization of local tax revenues that result, the average local tax collections for the city of Yogyakarta in 2002-2006 can be categorized as very efficient for the hotel tax, restaurant tax, entertainment tax, advertisement tax and street lighting tax with an average efficiency level below 10%. As for parking tax can be considered efficient with an efficiency of 21.24%. Overall contribution of local taxes in 2002-2006 had an average of 60.13%, where in 2002 the contribution rate reaches 63.65%. Key words: effectiveness, efficiency, local revenue.